The Impacts of Mergers and Acquisitions on firm performance. Using British examples - Liu, Danqing (2017)
Abstract This study is interested in examining how firms perform when they undertake M&As in terms of productivity by using accounting data. It employs 455 British mergers and acquisitions to examine the impact of M&As on firm performance during the period 1995-2006. The main findings of this study are that, in general, M&A activities have a positive impact on firm performance, for both the acquiring and acquired firms, and the target firm benefit more than the acquiring firm. For the short term we’ve observed (three years), the gains from M&As increase over time. Additionally, acquisition experience of the acquiring firm has a positive impact on the post-acquisition performance. Lastly, M&As that occur in different industries have different degrees of impacts on firm performance.